Identificação das atitudes dos pais e familiares frente ao uso da chupeta - Pereira, Eny Regina Bóia Neves [UNESP] (2004)
Due to an innate and natural reflex, most of the babies tend to have the strong necessity of sucking any and every object placed near their mouths. The pacifier, when rationally and temporally used, can provide for and supply this appeal. In these cases, this usage allows the perfect balance of the stomatognathic complex by effectively supporting the eruption and the position of the deciduous teeth, as well as the correct articulation of the words. The aim of this study is to present a piece of research fulfilled in tw0 day-cares in the cittes of bauru and piratininga – sp, involving children with minor social-cultural differences, in order to verify the opinion and attitude of parents in relation of the pacifier usage frequency, as well as the efects this habit may provoke. This research aroused a significant conclusion most parents tend to present a certain convenient accomodation regarding the pacifier usage, whereas others, nevertheless knowing the damagesits long-term use may provoke, are totally unaware of the severe alterations the pacifier may cause.